Adjuvant lung resection in the management of nontuberculous mycobacterial lung infection: A retrospective matched cohort study. (September 2018) - Aznar, María Luisa; Zubrinic, Marijana; Siemienowicz, Miranda; Hashimoto, Kohei; Brode, Sarah Kathleen; Mehrabi, Mahtab; Patsios, Demetris; Keshavjee, Shafique; Marras, Theodore Konstantine
Abstract: Background and objectives: Lung resection in patients with nontuberculous mycobacterial pulmonary disease (NTM-PD) is considered when medical therapy alone fails to provide long term control. Data regarding comparative and long-term outcomes are limited. We aimed to review indications and outcomes of adjuvant lung resection for NTM-PD compared with controls. Methods: We retrospectively studied 27 surgically treated patients, matched 1:1 for age, sex, NTM species, and radiologic pattern of disease, with control patients treated exclusively with antibiotics. Results: In the surgical group, the median (IQR) age was 55 (49–61) years and 74.1% were female. Eighteen patients had Mycobacterium avium complex, and 9 had M. xenopi . Operations included 8 pneumonectomies, 20 lobectomies, one segmentectomy and one lobectomy plus segmentectomy. Post-surgical complications occurred in 6 patients (20%), including 2 acute respiratory distress syndrome, 1 bronchopleural fistula, 1 pericardial tamponade, and 2 empyema. Complications were more common among patients operated upon for progressive disease despite medical therapy (OR 10, p = 0.025). Of 24 matched pairs followed for ≥1 year, sustained culture conversion was observed in 21 (87.5%) patients in the surgical group and in 11 (45.8%) patients in the non-surgical group (RR 2.36, 95%CI 1.37–4.03, p = 0.002). Median (IQR) percentage of follow-up time on antibiotics was 14% (0–100%) in the surgical group and 83% (10.8%–100%) in the non-surgical group (p = 0.195) during a median (IQR) follow-up of 16 (2–36) months. Conclusions: NTM-PD patients who underwent adjuvant lung resection experienced significant morbidity and more frequently achieved sputum culture conversion. Long term antibiotic requirements may have been reduced. Highlights: High rates of sputum culture conversion after lung resection. Recurrent NTM-PD common despite successful surgery. Long term radiologic deterioration may occur despite successful surgery. Adjuvant lung resection does not obviate the need for lifelong follow-up.